I’ve Never Been Able To Write! - Rejtő Jenő; Zachery Anderson ([sic])
I have never yet writtenCHAR(13) + CHAR(10) I’ve only scribbled this or that nor was it ever trueCHAR(13) + CHAR(10) I now can write and can see, what it is.CHAR(13) + CHAR(10) True.CHAR(13) + CHAR(10) Such truth as is reality itself, like that which is not like itselfCHAR(13) + CHAR(10) A mathematical dream:CHAR(13) + CHAR(10) An absolute good. On the cube.CHAR(13) + CHAR(10) Now I will write no more, I’ll merely jeer.CHAR(13) + CHAR(10) Jeer even Anatole France himself and I surely can write yet surely more can cry and even more can endure... if someone requires it of me.CHAR(13) + CHAR(10) It bothers me greatly that there is no reasoner... measurer.CHAR(13) + CHAR(10) Since I cannot write poetryCHAR(13) + CHAR(10) I’m trying it more often. Perhaps then it will be beautifulCHAR(13) + CHAR(10) The way kitsch was, like an alien continent,CHAR(13) + CHAR(10) Where never before have I walked and yetCHAR(13) + CHAR(10) Have led there among great dangers... othersCHAR(13) + CHAR(10) And could do it bravely.CHAR(13) + CHAR(10) And on a little branch I walked there myself.CHAR(13) + CHAR(10) I’ve just seen it. It was not a joy ride, just CHAR(13) + CHAR(10) what was shown to me by those fevered, willing friendsCHAR(13) + CHAR(10) Since then I’ve feared having a passion.CHAR(13) + CHAR(10) Like cocaine. Like this familiar moment (?)...CHAR(13) + CHAR(10) Hypnotized. Useful. Custom-made.